2018
DOI: 10.1097/cej.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase uptake of faecal tests for colorectal cancer screening: a systematic review

Abstract: International guidelines promote screening by faecal tests in asymptomatic individuals at average risk of colorectal cancer (CRC), but uptake does not reach recommended levels in most countries. The aim of this study was to synthetize evidence on (a) interventions aiming to increase uptake of faecal tests for CRC screening, in asymptomatic individuals at average risk of CRC, (b) interventions that targeted general practitioner (GP) involvement and (c) interventions that targeted nonresponders or disadvantaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 54 publications
3
49
0
Order By: Relevance
“…The current intervention was developed through a systematic multi-stage process combining theory, evidence and consultation with multiple stakeholders. Components found to improve uptake of retinopathy screening [38,43,72] and cancer screening [73][74][75][76][77][78][79][80][81][82], include audit and feedback [83], patient [73,76,77,79,[84][85][86][87][88][89][90][91] and physician [38,72] reminders, the use of trusted sources to deliver messages [37,[73][74][75] and key information leaflets [74,81,82]. Our intervention comprises these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The current intervention was developed through a systematic multi-stage process combining theory, evidence and consultation with multiple stakeholders. Components found to improve uptake of retinopathy screening [38,43,72] and cancer screening [73][74][75][76][77][78][79][80][81][82], include audit and feedback [83], patient [73,76,77,79,[84][85][86][87][88][89][90][91] and physician [38,72] reminders, the use of trusted sources to deliver messages [37,[73][74][75] and key information leaflets [74,81,82]. Our intervention comprises these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Some population‐based interventions have found FOBT/FIT to be particularly effective in boosting CRC screening uptake when kits are mailed to homes along with instructions and educational packages . Similarly, a systematic review revealed that outreach interventions including those utilizing mailed FOBT kits improved CRC screening in Canada, and several European countries . This initiative should be tested for potential scalability at the national level.…”
Section: Discussionmentioning
confidence: 99%
“…46,48,51 Similarly, a systematic review revealed that outreach interventions including those utilizing mailed FOBT kits improved CRC screening in Canada, and several European countries. 52 This initiative should be tested for potential scalability at the national level. Interventions are also needed at the level of care providers, given our finding of continued in-office screening and other studies pointing to knowledge gaps among health care providers.…”
Section: Model 2 (Sociodemographic Plus Crc Risk Factors)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors can influence screening participation including best-practice guidelines, physician reimbursement models, screening modalities available, physician recommendation for screening, the infrastructure and design of the screening programme itself, and participant-level factors 10–13. Interventions designed to increase screening participation are generally expensive, challenging to implement and have limited impact 14–16…”
Section: Introductionmentioning
confidence: 99%